EFFECTIVE HUMAN RESOURCE MANAGEMENT AND ENVIRONMENTAL SECURITY: PROTECTION OF HUMAN ENVIRONMENTAL RIGHTS AND CRITICAL INFRASTRUCTURE SUSTAINABILITY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The scientific paper aims to analyze the interaction between three main areas: the protection of environmental human rights, the resilience of critical infrastructure, and human resource management. These elements are interconnected and play an important role in developing and implementing effective management decisions and policies, combining environmental protection with care for human capital.The paper analyses key characteristics of environmental security as a dimension of the Human Security Concept, as well as the role of environmental rights. Additionally, the need to protect critical infrastructure in the context of environmental risks and threats is emphasized.The focus is placed on new aspects of human resource management, such as green human resources management, the role of so-called "green collars", employee motivation, and others. In this context, the role of effective human resource management in organizations that manage critical infrastructure is examined, to achieve sustainable outcomes in areas related to environmental security.The third fundamental element of the paper involves practical challenges in implementing the trends and new aspects described above. Ideas and practices are proposed to support the development of solutions for creating sustainable outcomes and policies in human resource management within the context of environmental security.